Sarcopenia does not affect clinical outcomes following lumbar fusion. (June 2019) - McKenzie, James C.; Wagner, Scott C.; Sebastian, Arjun; Casper, David S.; Mangan, John; Stull, Justin; Hilibrand, Alan S.; Vaccaro, Alexander R.; Kepler, Christopher
Highlights: Sarcopenia is defined as decreased muscular mass leading to decreased muscle function. Sarcopenia is associated with poor post operative outcomes after hip fracture surgery. Sarcopenia was not associated with worse outcomes in patients after lumbar surgery. Study outcomes were patient-reported at a mean followup of 18 months. Abstract: Sarcopenia, defined as decreased skeletal muscle mass or function, has recently been found to have increased perioperative morbidity and mortality. The relationship between sarcopenia and clinical outcomes in patients undergoing lumbar fusion has not been examined. This study investigates whether sarcopenia affects fusion rates and outcomes following single-level lumbar decompression and fusion. A retrospective analysis was undertaken of 97 consecutive patients who underwent a single level lumbar fusion for degenerative spondylolisthesis. Demographics, perioperative data, and patient reported clinical outcomes were collected. Measurements of paraspinal muscle CSA were made using a standardized protocol at the level of the L3-4 disc space on a preoperative lumbar MRI. Univariate analysis was used to compare cohorts with regards to demographics, comorbidities, and clinical outcomes. Of 97 patients, 16 patients (15.8%) were in the sarcopenic cohort utilizing a threshold of 986.1 mm 2 /m 2 . Reoperation rates were not significantly different between the two groups (0% vs 3.6%, p = .451). The sarcopenia cohort had lower BMI (28.1 vs 31.8, p = .017) and less male patients (6.3% vs 55.6%, p < .001). Mean follow-up was 18.3 months. There was no significant difference in postoperative Oswestry Disability Index (ODI) (24.7 vs 23.2, p = .794) Short Form 12 Physical (38.0 vs. 40.4, p = .445) Mental scores (55.5 vs. 53.6, p = .503), or visual analog scale (VAS) back pain scores (3.4 vs. 3.3, p = .818). No significant difference was found with regards to outcomes when comparing sarcopenic to non-sarcopenic patients undergoing lumbar fusion. Sarcopenia does not impact the clinical success of lumbar fusion for degenerative spondylolisthesis.